Danube Region – Analysis and Long-Term Development Trends of the Macro-Region - Gál, Zoltán; Lux, Gábor; Illés, Iván (Discussion Papers, 2013)
The Danube Region, perhaps the most complicated formation of the European continent, is based on physical geographical factors (the Danube, the river’s catchment area). The catchment area as a physical geographical framework forms a kind of water use and pollution unit, a focus, and through man-made transformation, it partially represents a kind of risk community as well. For people living in the area alongside the river itself, the proximity of the Danube represents a certain historical and cultural attitude. With the exception of the close riverbank area, the region’s population has only indirect Danube space consciousness. The region’s relief divides the Danube catchment area into several sub-catchment areas and natural units. The set of basins (Upper, Middle and Lower Danube Basin) potentially carries options for partial integration. Within some basins the intensification of co-operation may resolve the historically developed tensions, still partly existing today. This report is based on a synthesis of a number of sources listed in the bibliography, as well as original research by Institute staff. Its aim is not to provide a comprehensive analysis of the Danube transnational region as such, but well structured information useful enough to take into account the territorial specificities of this region when developing scenarios at the European level. To this end, it presents the most relevant sectoral trends affecting the Danube Region at the present time, as well as domestic and EU policy challenges and development opportunities. On the basis of analysis, development scenarios are outlined, also identifying the key trends which will influence integration and Europeanisation in the forthcoming decades.